Pengaruh Gadget Terhadap Perkembangan Bahasa Anak Usia 3-6 Tahun Di Kota Makassar - A. Nurul Febriani; Asaria Citra Dewi; Syamsuardi Syamsuardi; Muhammad Akil Musi; Parwoto Parwoto (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2024)
The presence of Gadgets has become an integral part of everyday life, including in the Early Childhood environment. In this modern era, children are exposed to technology that is made to facilitate human life in this increasingly advanced era. They are often exposed to a variety of multimedia content, which can affect their language, understanding and the way they communicate. The essence of education is actually given from an early age to help the development of children. A child's ability to recognize themselves and their surroundings as well as increased awareness related to their physical growth is called child development. Language development is one of the many developments that young children experience. Parents, educators and researchers are very concerned about the influence of devices on children's language development. However, there are doubts about whether the use of devices can affect children's language ability. The purpose of this study was to determine the effect of gadgets on the language development of children aged 3-6 years in Makassar City, The type of research used was quantitative. The research instrument used a questionnaire